A NOVEL IMAGE THEFT IDENTIFICATION USING BIOMETRIC FEATURE - Fernandez, Jincy J; Pandian, Nithyanandam; Chavali, Raghuvamsh; Appalaghe, Ashwanth Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
In today's internet world, all the data are represented and stored in digital form. Almost any entity in this world can be represented digitally, rangingÂ from simple text to complex multimedia work. Now, the challenge is to claim the ownership and prevent theft of one's own digital data. MultimediaÂ theft has driven the attention of many stakeholders who spend huge money and precious time in creating or making such valuable digital data. AmongÂ all the multimedia entities, image files are more vulnerable for theft since it is the basic component of any visuals. The notion of this research work isÂ to propose an image theft detection model which will determine whether partial theft or complete theft of an image has occurred or not. A biometricÂ feature, i.e., fingerprint of the owner is embedded on the digital image at a micro level, such that even a very small portion of image theft can beÂ determined, and the ownership of the image can be claimed by the owner. This research is limited to the spatial domain, i.e. raw image. AssessmentÂ metrics of the results shows that embedding the biometric feature on an image does not distort the image quality and its artifacts.